Cardiovascular Manifestations of COVID-19 - Butt, Nausharwan; Ahmad, Huzaifa; Khalid, Nauman; Ahmad, Sarah Aftab; Pahwa, Nancy; Talwar, Gagandeep Singh; Chhabra, Lovely (Archives of Clinical and Biomedical Research, 2020)
Novel Coronavirus 2019 (COVID-19) has spread within a short period of time from Wuhan, a city within central China, to cause a global pandemic. Treatment options remain limited and mortality is high in older patients. Although primarily linked to respiratory symptoms, cardiac complications have been found to be common and can also be severe. Various cardiac manifestations may include myocarditis, ST elevation myocardial infarction (STEMI), non-ST-elevation myocardial infarction (NSTEMI), pericarditis or myopericarditis, pericardial effusion, stress (Takotsubo) cardiomyopathy and cardiac arrhythmias. COVID-19 related cardiovascular diseases present a diagnostic challenge, given overlapping features. Fear of infection has resulted in more frequently seen late presentations to hospitals causing greater morbidity and mortality. In addition, regional and hospital workflows have been disrupted due to the virus which has also led to significant delay in patients receiving urgent care. Furthermore, optimal patient care delivery has to be balanced against the risk of infection to health care providers and limited resource management. In addition, regional and hospital workflows have been disrupted due to the virus which has also led to significant delay in patients receiving urgent care. Furthermore, optimal patient care delivery has to be balanced against the risk of infection to health care providers and limited resource management. Off-label drugs used to treat the infection have largely been unsuccessful. Initial proposed guidelines addresses some concerns; however, further comprehensive literature is required to develop standardized management. Vaccine development at this time remains the only proposed definitive prevention strategy though a definitive timeline for such a modality currently remains uncertain. Given the continued pandemic, health care providers are adjusting their practices to adapt with new soc